Innovative Technologies in School Geography Classes as a Part of a State Education Policy in Kazakhstan and Kyrgyzstan - Toksonbaev, Ryskeldy N.; Nurgaziev, Yermek U. (International Journal of Psychosocial Rehabilitation, 2020)
The second half of the 20th century in teaching can be characterized as a time constant changes in the educational structure, which tried to adapt to external influences. Schooling process in Kazakhstan and Kyrgyzstan, along with similar processes of most European’s countries, has undergone numerous changes, including radical ones. The 21st century brought to these Central Asian countries new guidelines in the education system, which are consistent with the global target perspective of the state. The methods and approaches that provide the evolutionary leap in the educational system and help to cultivate the necessary qualities in students became priority.